2022
DOI: 10.48550/arxiv.2207.03302
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Black holes in dS$_3$

Abstract: In three-dimensional de Sitter space classical black holes do not exist, and the Schwarzschild-de Sitter solution instead describes a conical defect with a single cosmological horizon. We argue that the quantum backreaction of conformal fields can generate a black hole horizon, leading to a three-dimensional quantum de Sitter black hole. Its size can be as large as the cosmological horizon in a Nariai-type limit. We show explicitly how these solutions arise using braneworld holography, but also compare to a no… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1
1

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 78 publications
1
1
0
Order By: Relevance
“…Including semi-classical backreaction, the first law of horizon thermodynamics was modified such that the classical entropy is replaced by the generalized entropy. This is expected to be a feature for systems which include backreaction; indeed, the same modification appears in the three-dimensional semi-classical Schwarzschild-de Sitter black hole [93]. Further, in the microcanonical ensemble we found that the generalized entropy is equal to the microcanonical entropy, whose stationarity condition implies extremizing the generalized entropy, similar to recent results for eternal AdS 2 black holes [30].…”
Section: Discussionsupporting
confidence: 88%
“…Including semi-classical backreaction, the first law of horizon thermodynamics was modified such that the classical entropy is replaced by the generalized entropy. This is expected to be a feature for systems which include backreaction; indeed, the same modification appears in the three-dimensional semi-classical Schwarzschild-de Sitter black hole [93]. Further, in the microcanonical ensemble we found that the generalized entropy is equal to the microcanonical entropy, whose stationarity condition implies extremizing the generalized entropy, similar to recent results for eternal AdS 2 black holes [30].…”
Section: Discussionsupporting
confidence: 88%
“…It would also be interesting to adapt our formalism to three-dimensional spacetimes, such as the BTZ black hole [58], its quantum and de Sitter generalizations [59,60], or generalized threedimensional solutions described in [61,62]. To this end, it would be worthwhile to also attempt to extend the Cotton double copy [63] to include external sources.…”
Section: Discussionmentioning
confidence: 99%